Anxiety levels moderate the association between visual acuity and health-related quality of life in chronic eye disease patients - Hugo Senra (2022)
The current study examines the potential moderating effect of depression and anxiety on the relationship between visual acuity and health-related quality of life in patients with chronic eye diseases. Of the 71 patients, 37 (52%) were female and 34 (48%) were male, age (mean ± SD) was 69 ± 12 years. A significant multivariate regression model was found for patients' health-related quality of life (EQ-5D-5L index) (R2 = 0.43, p < 0.001), in which visual acuity (logMAR) (p < 0.001), anxiety (HADS-A) (p = 0.007), and age of diagnosis (p = 0.04)  were independently associated with health-related quality of life (EQ-5D-5L). The moderation model for anxiety (R2 = 0.47, F = 5.91, p < 0.001) revealed a significant interaction of visual acuity and levels of anxiety in relation to health-related quality of life. Conditional effects analysis suggested that higher logMAR values (which indicate more vision loss) were associated with lower EQ-5D-5L index (indicating worse health-related quality of life), this relationship being stronger (even more negative), when levels of anxiety are high. Clinical and rehabilitation services providing care for chronic eye disease patients should include regular checks for patients' levels of anxiety, even in patients who still have preserved visual acuity, to help preventing a synergistic source of long-term poor quality of life and disability.